The Influence of Social Media Marketing and Price Perception on Hospital Brand Image and Its Influence on Hospital Choice Intention at Xyz Orthopedic Hospital in Jakarta - Johan Qomarasandhi (Eduvest - Journal of Universal Studies, 2025)
XYZ Orthopaedic Hospital in Jakarta faces declining patient acquisition and challenges in converting clinic visits into elective surgeries, which are its primary revenue streams. This study explores the effects of social media marketing and price perception as one of the antecedents to hospital brand image and their impact on hospital choice intention, with health literacy as moderating variables. A cross-sectional study was conducted with 134 respondents recruited from outpatient clinics at XYZ Orthopaedic Hospital. Data were collected using a structured questionnaire and analysed through Structural Equation Modelling (SEM). Variables measured included Word of Mouth (WoM), Hospital Social Media, Patient Review, Hospital Advertisement, Price Perception, Surgeon Reputation, Hospital Brand Image, Health Literacy, and Hospital Choice Intention. Word of Mouth, Surgeon Reputation, and Price Perception have significant impact toward Hospital Brand Image while Hospital brand image itself does not have an impact towards Hospital Choice Intention unlike Surgeon Reputation (R= 0.440, p<0.05). The Overall model has an R2 of 0.690. Importance Performance Map Analysis shows that without Hospital Brand Image, Price Perception of this hospital needs significant improvement and very important, but when accounts for the hospital brand image, the price perception becomes less important. Enhancing word of mouth, price competitiveness and emphasizing surgeon reputation are critical for improving hospital brand image. With a stronger hospital brand image, one can price more freely towards patients.